(untitled) (Trento Student Law Review, 2022)
The paper aims to provide an overview on sting operations facilitating crimes and entrapment defense, related to public corruption behaviors. A historiographic introduction will show how the U.S. system has managed corruption from the XVIII century; afterward, the focus will shift on the dogmatic profiles to clarify complications and practical functioning of entrapment defense as to the general theory of the offense. A reflection is also needed on whether or not the agent provocateur figure should be imported into European systems, displaying how case law from the Italian Supreme Court are inspired by the Grand Chamber of the European Court of Human Rights in Strasbourg: despite theoretical discrepancies, both these courts are in a constant, however silent, dialogue with the U.S. courts. The crucial issue is the analysis of legal principles pertinent to the agent provocateur and to the instigated individual in order to understand, from the European point of view, whether or not the former is indictable and, from the U.S. point of view, whether or not the latter is.